2021
DOI: 10.1021/acsomega.1c01611
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial PDMS Surfaces Prepared through Fast and Oxygen-Tolerant SI-SARA-ATRP, Using Na2SO3 as a Reducing Agent

Abstract: Poly­(dimethylsiloxane) (PDMS) is an attractive, versatile, and convenient material for use in biomedical devices that are in direct contact with the user. A crucial component in such a device is its surface in terms of antimicrobial properties preventing infection. Moreover, due to its inherent hydrophobicity, PDMS is rather prone to microbial colonization. Thus, developing an antimicrobial PDMS surface in a simple, large-scale, and applicable manner is an essential step in fully exploiting PDMS in the biomed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Earlier, multiple studies reported a reduction in the viability of bacterial pathogens when exposed to antibacterial surfaces. 61 , 62 , 63 However, the present study demonstrated that investigating bacteria-laden drop impact on surfaces is highly relevant from the disease transmission perspective. This novel approach to droplet impact study opens a new dimension that brought out the effect of impact velocity-induced mechanical stress and evaporation-induced desiccation stress on the survival of bacteria in the nutrient-rich and nutrient-deficient medium.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier, multiple studies reported a reduction in the viability of bacterial pathogens when exposed to antibacterial surfaces. 61 , 62 , 63 However, the present study demonstrated that investigating bacteria-laden drop impact on surfaces is highly relevant from the disease transmission perspective. This novel approach to droplet impact study opens a new dimension that brought out the effect of impact velocity-induced mechanical stress and evaporation-induced desiccation stress on the survival of bacteria in the nutrient-rich and nutrient-deficient medium.…”
Section: Discussionmentioning
confidence: 79%